2015
DOI: 10.1111/j.1564-913x.2015.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic growth, labour flexibilization and employment quality in Colombia, 2002–11

Abstract: Over the period 2002–11, the Colombian labour market saw a marked improvement in employment opportunities, accompanied by an increase in nonstandard forms of employment. The authors look at how this affected employment quality, using a composite index based on Categorical Principal Components Analysis (CATPCA). They observe a small but widespread improvement in employment quality – mainly for self‐employed women – brought about by higher earnings, increased social protection and less time‐related underemployme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 4 publications
0
7
1
2
Order By: Relevance
“…It was shown in a study conducted in Colombia that self-employed women reported improvements in the quality of employment evaluated by parameters such as: (1) social security coverage, (2) earnings, (3) social dialogue, (4) job satisfaction, and (5) reconciling work and family life. Earnings were identified as the factor most relevant to improving the quality of employment (Farné and Vergara, 2015).…”
Section: Working In Nonstandard Forms Of Employment According To Gender: Results Of a Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown in a study conducted in Colombia that self-employed women reported improvements in the quality of employment evaluated by parameters such as: (1) social security coverage, (2) earnings, (3) social dialogue, (4) job satisfaction, and (5) reconciling work and family life. Earnings were identified as the factor most relevant to improving the quality of employment (Farné and Vergara, 2015).…”
Section: Working In Nonstandard Forms Of Employment According To Gender: Results Of a Literature Reviewmentioning
confidence: 99%
“…In addition, these forms are considered to have the characteristics of precarious employment, indicating a low degree of meeting employee interests (Jacquemond and Breau, 2015). Furthermore, the benefits of the use of nonstandard forms of employment for women are highlighted by the possibility of more flexibility combining work with family life, creating the conditions for the labor activation of women, and, in some nonstandard forms of employment, such as self-employment, the possibility of meeting employees' business ambitions and earning higher incomes (Tonkikh et al, 2019;Buribayev and Khamzina 2019;Farné and Vergara 2015).…”
Section: Introductionmentioning
confidence: 99%
“…7 We selected two types of groups; 8 the dimension used for considering the homogeneity of each group was the segment of the labor market in which the members participate. The reason for this is that the labor market segmentation is fairly strong between low and high quality jobs (Farné and Vergara 2015;Combarnous and Deguilhem 2016). In addition, this dimension is linked with income and socioeconomic strata, which summarizes most of the institutional differences in Colombia.…”
Section: Quantitative and Qualitative Datamentioning
confidence: 99%
“…Confronted with this contrasting literature reviews, we built an original theoretical framework to explain why these heterogeneous results have been observed. We started from the idea of heterogeneity between different social groups in terms of ex post job quality, and we assumed that a clear distinction exists between high and low job quality groups in the labor market (Farné and Vergara 2015;Combarnous and Deguilhem 2016). To obtain a job, a worker may have used different means with distinct effects depending on his group (Bentolila et al, 2010).…”
Section: Quantitative and Qualitative Datamentioning
confidence: 99%
See 1 more Smart Citation